2001
DOI: 10.3758/bf03200458
|View full text |Cite
|
Sign up to set email alerts
|

Structural alignment facilitates the noticing of differences

Abstract: The perception of likeness is practically very much bound up with that of difference.That is to say, the only differences we note as differences, and estimate quantitatively,and arrange along a scale, are those comparativelylimited differences which we find between members of a common genus. (James, 1890, Vol. 1, p. 528) How are differences generated and why are certain differences noticed and others are not? The answer may depend on whether or not differences bear any relationship to commonalities. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 32 publications
10
102
0
5
Order By: Relevance
“…Why does seeing the blue and yellow (and purple and orange) spoon side-by-side make more explicit the relation between color and function? Gentner and her colleagues (Gentner, 1983;Gentner & Gunn, 2001;Gentner & Markman, 1994;Gentner & Medina, 1998;Markman & Gentner, 1997 have argued that when attempting to map one event representation onto another, there are multiple strategies that can be invoked. One strategy is to focus on the objects themselves, and to identify whether the object in the first event (e.g., blue spoon) maps onto the object in the second event (e.g., yellow spoon).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Why does seeing the blue and yellow (and purple and orange) spoon side-by-side make more explicit the relation between color and function? Gentner and her colleagues (Gentner, 1983;Gentner & Gunn, 2001;Gentner & Markman, 1994;Gentner & Medina, 1998;Markman & Gentner, 1997 have argued that when attempting to map one event representation onto another, there are multiple strategies that can be invoked. One strategy is to focus on the objects themselves, and to identify whether the object in the first event (e.g., blue spoon) maps onto the object in the second event (e.g., yellow spoon).…”
Section: Discussionmentioning
confidence: 99%
“…In children, comparison has been identified as important to analogical reasoning (Gentner & Namy, 2006;Gentner & Toupin, 1986), detecting relational similarities (Kotovsky & Gentner, 1996), spatial mapping (Loewenstein & Gentner, 2001), and the development of categories (Gentner & Namy, 1999). Finally, cognitive psychologists have investigated the importance of comparison to a number of cognitive functions, including analogy, memory, representational mapping (Gentner, 1983;Gentner & Gunn, 2001;Markman & Gentner, 1997. Together these results firmly establish comparison as an integral part of cognitive function, across the life span.…”
Section: The Role Of Comparison In Forming Categorical Event Represenmentioning
confidence: 95%
See 1 more Smart Citation
“…Structural alignment accounts for the relations between the features of a single stimulus, but it often underestimates perceived similarity because it fails to account for the relation between two stimuli. In fact, Gentner and Brem (1999; see also Gentner & Gunn, 2001) reject thematic relations as a legitimate source of similarity. In their view, similarity is synonymous with comparison (i.e., structural alignment); therefore, any other process that influences a similarity task (e.g., thematic integration) is considered illegitimate.…”
mentioning
confidence: 99%
“…Gentner and Gunn (2001) presented pairs of concepts and instructed participants to list either thematic relations between the items or commonalities. They found that the two tasks had different effects on the subsequent processing of those stimuli: Whereas listing thematic relations inhibited the detection of differences between concepts, listing commonalities facilitated the detection of differences.…”
mentioning
confidence: 99%